Recovery of salty soil. Workshop report on the construction of a guidebook - Ba, Marième Fall; Fall, Dioumacor; Touré, Katim; Mbaye, Modou; Ndiaye, Ababacar; Diop, Birame; Diop, Penda; Ndiaye, Moussa; Thiaw, Mame Arona; Piraux, Marc; Mbaye, Tamsir (2024)
This report reviews the main stages of the workshop organized by teams from ISRA/CNRF, CIRAD and their partners and held from May 14 to 17, 2024. Objective was to was to develop a tool for the optimal scaling-up of best practices in the recovery and reclamation of saline soils. T